Combining the Continuous Integration Practice and the Model-Driven Engineering Approach - García-Díaz, Vicente; Pascual Espada, Jordán; Núnez-Valdéz, Edward Rolando; Pelayo G-Bustelo, B. Cristina; Cueva Lovelle, Juan Manuel (Computing and Informatics, 2016)
The software development approach called model-driven engineering has become increasingly widespread. The continuous integration practice has also been gaining the importance. Some works have shown that both can improve the software development process. The problem is that the model-driven engineering is still a very active research topic lacking its maturity, what translates into difficulties in optimal incorporation of the continuous integration practice in the process. We present an experience report in which we show the problems we have detected in a real project and how we have solved them. Thus, we increase the productivity of development and the non-technical people are able to modify already deployed applications. Finally, we incorporate an evaluation that shows the benefits of the proposed union.